A neurophylogenetic approach provides new insight to the evolution of Scaphopoda. Issue 6 (21st October 2015) - Sumner‐Rooney, Lauren H.; Schrödl, Michael; Lodde‐Bensch, Eva; Lindberg, David R.; Heß, Martin; Brennan, Gerard P.; Sigwart, Julia D.
SUMMARY The position of scaphopods in molluscan phylogeny remains singularly contentious, with several sister relationships supported by morphological and phylogenomic data: Scaphopoda + Bivalvia (Diasoma), Scaphopoda + Cephalopoda (Variopoda), and Scaphopoda + Gastropoda. Nervous system architecture has contributed significant insights to reconstructing phylogeny in the Mollusca and other invertebrate groups, but a modern neurophylogenetic approach has not been applied to molluscs, hampered by a lack of clearly defined homologous characters that can be unequivocally compared across the radical body plan disparity among the living clades. We present the first three‐dimensional reconstruction of the anterior nervous system of a scaphopod, Rhabdus rectius, using histological tomography. We also describe a new putative sensory organ, a paired and pigmented sensory mantle slit. This structure is restricted to our study species and not a general feature of scaphopods, but it forms an integral part of the description of the nervous system in R. rectius. It also highlights the potential utility of neuro‐anatomical characters for multiple levels of phylogenetic inference beyond this study. This potential has not previously been exploited for the thorny problem of molluscan phylogeny. The neuroanatomy of scaphopods demonstrates a highly derived architecture that shares a number of key characters with the cephalopod nervous system, and supports a Scaphopoda + Cephalopoda grouping.